Development of an Ethnophysics-Based Critical Thinking Test on Heat Concept - Siti Nurhaliza; Delthawati Isti Ratnaningtyas; I Komang Werdhiana; Syamsuriwal Syamsuriwal (Kasuari: Physics Education Journal (KPEJ), 2026)
Critical thinking skills are important in physics education because they encourage students to analyze, evaluate, and apply concepts in real life. However, the assessment instruments used still focus on memory skills and have not integrated the local cultural context. In fact, many physical phenomena, including heat transfer, can be seen in cultural activities such as traditional food preparation. Previous studies have emphasized the development of questions based on higher-order thinking skills, literacy, and numeracy, but few have linked them to culture. Therefore, it is necessary to develop ethno-physics-based critical thinking questions on heat so that assessments not only measure conceptual mastery but also connect physics with local wisdom. This study aims to analyze the validity, reliability, discriminating power, and difficulty level of ethno-physics-based critical thinking questions on the topic of heat, as well as to test their practicality. The method applied is Tessmer's Research and Development (R&D) model, with stages including Preliminary, Self-Evaluation, and Formative Evaluation. The results of the development show that the resulting test items are valid. The reliability value obtained is 0.75, which is classified as high. In terms of difficulty, the majority of questions are categorized as moderate and a small portion are easy. The discrimination power of the test items varies between very good, good, and fair. Overall, all items successfully differentiated between students' abilities, and none of the items failed to differentiate. In terms of practicality, the use of these items is classified as very practical.